Gender-Biased Expectations of Altruism in Adolescents - Salgado, Mauricio (Frontiers in Psychology, 2018)
Research suggests that women, but not men, manifest gender-biased expectations of altruism: while women expect other women to be more altruistic, men expect women to be as generous as men. Do adolescents expect women and men to behave differently regarding altruism? I analyse adolescents' gender beliefs about altruism using a modified Dictator Game. Results indicate that adolescents believe that others of same gender are more altruistic than others of the opposite gender. I also found that adolescents' agreement with the existence of different societal roles for men and women moderates the relationship between gender and gender beliefs. Although it was expected that adolescents who agree with different gender roles would expect women to be more generous, surprisingly, the results presented here confirm this only for male adolescents, but in the opposite direction: the more they agree with the existence of different gender roles, the more they seem to believe that men are more generous than women. Instead, female adolescents believe that women are more altruistic unconditionally. Thus, the previously documented bias seems to be already in place during adolescence, above and beyond other confounding factors. However, the identified gender-biased expectations of altruism are conditional upon normative judgements regarding the existence of gender roles in society, presumably acquired via socialisation.